1989
DOI: 10.1093/ptj/69.6.501
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric Validation of the Caltrac® Accelerometer During Level Walking

Abstract: The primary purpose of this study was to compare the Caltrac accelerometer output with measured energy expenditure (Ee). Twenty-five volunteers (10 men, 15 women) walked on a level motor-driven treadmill at four different speeds (54, 81, 104, and 130 m.min-1) with the Caltrac device affixed to the waistline. Each of the four experimental trials lasted eight minutes, and the testing was completed within an hour. During the test, oxygen consumption (VO2) (in L.min-1 and in mL.kg-1.min-1) and nonprotein respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
4

Year Published

1991
1991
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 6 publications
3
22
0
4
Order By: Relevance
“…The best prediction of EE~,.t was obtained from the measured IMA variables at the lower back (r=0.92-0.97). These results are comparable to those reported by Balogun et al and Haymes and Byrnes, who reported correlations of 0-92 and 0-94, respectively, between energy and expenditure and IMA measured in vertical direction with a body-fixed uniaxial accelerometer at waist level during walking (BALOGUN et al, 1989;HAYMES and BYm'qES, 1993). The influence of accelerometer orientation on IMA was evident, especially at the limbs and during the lowest walking velocities.…”
Section: Discussionsupporting
confidence: 89%
“…The best prediction of EE~,.t was obtained from the measured IMA variables at the lower back (r=0.92-0.97). These results are comparable to those reported by Balogun et al and Haymes and Byrnes, who reported correlations of 0-92 and 0-94, respectively, between energy and expenditure and IMA measured in vertical direction with a body-fixed uniaxial accelerometer at waist level during walking (BALOGUN et al, 1989;HAYMES and BYm'qES, 1993). The influence of accelerometer orientation on IMA was evident, especially at the limbs and during the lowest walking velocities.…”
Section: Discussionsupporting
confidence: 89%
“…These correlations are higher than those found for standardized activities in the laboratory using the uniaxial Caltrac [6], [39]- [41] or the TA of Meijer et al [5], [23]. Discrepancies between measured and estimated values of during high-intensity activities and low intensity activities were also smaller than those reported for the Caltrac [17]- [19] and the accelerometer of Meijer et al [23].…”
Section: Discussionmentioning
confidence: 54%
“…Reproducibility of acceleration counts measured at the low back during various exercises was good ( 0.94) and a pooled correlation coefficient of 0.74 was found for the relationship between acceleration count and energy expenditure [6]. From more recent studies it can be concluded that Caltrac output shows good correlation with measured energy expenditure during separate well-defined activities in the laboratory, like treadmill walking ( 0.68-0.94), but generally overestimates energy expenditure under these circumstances [17], [18]. Under freeliving conditions the uniaxial Caltrac can be used to distinguish among interindividual levels of daily physical activity, but tends to systematically underestimate the energy requirements when compared to whole body indirect calorimetry [19] or the doubly labeled water method [20], [21].…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, many studies have attempted to test the accuracy of accelerometry for assessing walking speed and the related energy expenditure. Good correlation was found between walking speed and the integral of the modulus of body acceleration in 0% slope conditions (BALOGUN et al 1989). Under variable uphill or downhill conditions, however, prediction of speed or energy expenditure is not possible (MELANSON andFREEDSON, 1995, TERRIER et al, 1999).…”
Section: In Final Form 4 January 2000mentioning
confidence: 91%